Reproductive Biology of Calamus Manan Miquel - Alloysius, David (1999)
Adopting a plant improvement programme that combines silviculture and genetic improvement could increase yields of Calamus manan plantations. The silviculture of C. manan is well studied but not on the aspects of genetic improvement. Information on reproductive biology, which is one of the basis for all genetic improvement programmes, is still lacking for C. manan. The objective of this study was therefore to investigate the reproductive biology of C. manan. The study was done in a rattan plantation located at Luasong. Tawau, Sabah. The floral morphology of C. manan was common for species in genus Calamus. Observations showed that C. manan flowered annually but with different intensities. The inflorescence emergence normally occurred in October - December and fruits matured 16-17 months after. No clear relationship was detected between inflorescence emergence and meteorological parameters. Anthesis in male plants (41 days) was found to be longer than in female plants (25 days). There were about 60,000 and 9,000 pollen grains in pre-anthesis and fallen flowers, respectively. C. manan pollens could maintained half of its initial viability for four, eight and twelve weeks if desiccated and stored at 25°C, 4°C and -18°C, respectively. Anthesis occurred at night, suggesting the important role of nocturnal insects especially moths in pollination. Bees were proposed as pollinators during the daytime. A controlled pollination experiment was conducted to determine the best pollination bag and the differences between fresh and stored pollens in effecting fertilization. The sex ratio in a planted population was found to be male-biased but had a tendency to move towards unity as the age of the stand increased. The fruit production capacity of C. manan increased as the plants grew older. The implications of the reproductive characteristics on plantation establishment of C. manan are discussed.